Student Learning Habits Seen From The Type of School - Popy Sri Jelita; Afrizal Sano (Jurnal Neo Konseling, 2019)
The type of research used is quantitative with a comparative descriptive approach. The population  in this study were students of SMPN 15 Padang and MTsN 1 Padang with a total of 887 students from both schools and a total sample of 265 students from both schools taken by simple random sampling technique. The data collection tool used was a questionnaire with a Likert scale. The results of this study show that: (1) overall the learning habits of students at SMPN 15 Padang and MTsN 1 Padang are in the good category with a percentage of 85.5%, (2) the learning habits of students in SMPN 15 Padang are in the good category with a percentage of 62% and the study habits of students in MTsN are in the good category with a percentage of 68%, and (3) the t-test states that there are significant differences regarding the learning habits of students at SMPN 15 Padang and MTsN 1 Padang, which average student learning habits in MTsN 1 Padang are better than students at SMPN 15 Padang.